Stain Removal Potential of Strawberry Strips Against Extrinsic Stains on the Tooth Surface Of Adolescents Aged 18-25 years old - Fitri, Elmalia; Suwondo, Ari Suwondo,; Supriyana, Supriyana (Universitas Padjadjaran, 2025)
Extrinsic stain is a staining of teeth that is attached directly to the surface of the tooth. Disorders caused by stains are causing aesthetic problems that can have a considerable psychological impact, especially if they occur in the anterior tooth. Stains are difficult to clean just by brushing your teeth. Utilizing natural strawberry ingredients as Stain Removal Strips for an alternative to cleaning extrinsic stains on the surface of teeth. Proven administration of Stain Removal Strips strawberry extract (Fragaria x Ananassa) effectively cleans extrinsic stains on the surface of teeth. This study used the Quasy experimental method with a pretest posttest design with control group. Research sampling was carried out by purposive sampling. The sample consisted of 20 people divided into 2 groups. The control group with 6% hydrogen peroxide strips and the intervention group with 40% strawberry extract stain removal strips twice a day with a duration of 30 minutes for 7 days. The results showed that giving strawberry extract Stain Removal Strips was 40% effective in cleaning extrinsic stains on day 3 and day 7 against extrinsic stains on the tooth surface with values of p = 0.009 and p = 0.002 (p < 0.05) compared to the control group. Stain Removal Strips 40% strawberry extract has potential as an alternative to cleaning extrinsic stains on tooth surfaces. Keywords: Strawberry, Extrinsic Stain.